Swedish crime fiction : novel, film, television - Peacock, Steven (Manchester University Press, 2014)
Swedish crime fiction" became an international phenomenon in the first decade of the twenty-first century, starting with novels but then percolating through Swedish-language television serials and films and on to English-language BBC productions and Hollywood remakes. This books looks at the rich history of "Nordic noir" examines the appeal of this particular genre and attempts to reveal why it is distinct from the plethora of other crime fictions....